Incremental Healthcare Costs and Outpatient Antifungal Treatment of Patients with Aspergillosis in the United States - Emily Durden; Donna McMorrow; Paul Juneau; Robert Fowler; Paresh Chaudhari; David Horn (Journal of Health Economics and Outcomes Research)
**Objectives:** To evaluate the total and outpatient economic burden of aspergillosis, and to describe the outpatient antifungal treatment of aspergillosis within a large, commercially-insured population in the United States.